Violent behavior of juveniles in a multiethnic society: effects of personal characteristics, urban areas, and immigrants' peer networks - Windzio, Michael (Journal of ethnicity in criminal justice, 2009)
Using data from a large school survey based on 14,301 cases, we examined several risk factors, such as low self-control, culture of honor, and social bonds, for juvenile violence among immigrant and native-born Germans. Our empirical analyses indicate that violent peer networks and low self-control are more relevant for the explanation of juvenile violence than culture of honor. Moreover, these risk factors are also a consequence of the spatial concentration of Turkish and other immigrants living in large German cities. In these cities, culture of honor as well as low self-control (high temper) are more prevalent. Hence, residence in large cities could contribute to an explanation of why some immigrant groups exhibit higher risk than natives. Therefore, further research should focus more on social environments like networks and the residential segregation of juveniles from immigrant background living in larger cities.